2005
DOI: 10.1179/016164105x25324
|View full text |Cite
|
Sign up to set email alerts
|

Acute vertebrobasilar occlusion: current treatment strategies

Abstract: Our findings suggest that the trigemino-cervical reflex could be useful in the clinical assessment of TN prior to instituting non-surgical treatment. The bilateral location of the abnormalities in some patients seems to point to a centrally located dysfunction; therefore, this study supports the idea that mechanisms in the central nervous system may play an important role in the pathophysiology of trigeminal neuralgic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…650,662,663 When there is angiographic evidence of thrombus at the origin or extracranial portion of the vertebral artery, anticoagulation is generally recommended for at least e100 Circulation July 26, 2011 3 months, whether or not thrombolytic therapy is used initially. 662,664 -666 The WASID (Warfarin versus Aspirin for Symptomatic Intracranial Disease) trial found aspirin and warfarin to be equally efficacious after initial noncardioembolic ischemic stroke.…”
Section: Recommendations For Management Of Atherosclerotic Risk Factomentioning
confidence: 99%
“…650,662,663 When there is angiographic evidence of thrombus at the origin or extracranial portion of the vertebral artery, anticoagulation is generally recommended for at least e100 Circulation July 26, 2011 3 months, whether or not thrombolytic therapy is used initially. 662,664 -666 The WASID (Warfarin versus Aspirin for Symptomatic Intracranial Disease) trial found aspirin and warfarin to be equally efficacious after initial noncardioembolic ischemic stroke.…”
Section: Recommendations For Management Of Atherosclerotic Risk Factomentioning
confidence: 99%
“…[306][307][308][309] The WASID (Warfarin versus Aspirin for Symptomatic Intracranial Disease) trial found aspirin and warfarin to be equally efficacious after initial noncardioembolic ischemic stroke. 310,311 Ticlopidine was superior to aspirin for secondary prevention of ischemic events in patients with symptomatic posterior circulation disease.…”
Section: Evaluation Of Patients With Vertebral Artery Diseasementioning
confidence: 99%
“…For patients with acute ischemic syndromes that involve the vertebral artery territory and angiographic evidence of thrombus in the extracranial portion of the vertebral artery, anticoagulation is generally recommended for at least 3 months, whether or not thrombolytic therapy is used initially (306)(307)(308)(309). The WASID (Warfarin versus Aspirin for Symptomatic Intracranial Disease) trial found aspirin and warfarin to be equally efficacious after initial noncardioembolic ischemic stroke (310,311).…”
Section: Medical Therapy Of Patients With Vertebral Artery Diseasementioning
confidence: 99%